Toxicity of chlorinated aromatic compounds in animals and humans: in vitro approaches to toxic mechanisms and risk assessment. - Greenlee, W F (1985)
Human exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and chlorinated analogs commonly results in pathological changes in the skin and its appendages characterized by thickening of the epidermis (acanthosis), hyperkeratosis and squamous metaplasia of the epithelial lining of the sebaceous glands. Acneform lesions (chloracne) develop as hair follicles dilate and fill with keratin and sebaceous glands become cystic. In animal models it has been found that the chloracneogenic potential of the halogenated aromatic compounds examined corresponds with the relative affinity of these same compounds for the cytosolic TCDD receptor. This receptor controls the coordinate expression of a number of inducible enzyme activities and in certain cell targets can alter normal programs of proliferation and differentiation. In this report we describe some of our ongoing studies on the mechanisms of action of TCDD in normal human epidermal cells and squamous cell carcinoma (SCC) lines. These systems permit detailed investigation of the molecular and biochemical events underlying pathologic changes in the skin and offer the potential of establishing a risk assessment model for halogenated aromatic compounds by using human target cells.